HUMOR PADA SALESPERSON AUTO 2000 PT. “X” DI JAKARTA BERDASARKAN TINJAUAN PSIKOLOGI ULAYAT - Michael Michael; Shanty Sudarji (Psibernetika, 2014)
This study aims to determine how the humor in the salesperson at Auto 2000 in Jakarta based on a review of Indigenous Psychology. Research instruments using open-ended questionnaire that is based on the results of focus group discussion. Answers were analyzed using thematic analysis method. Number of subjects , 134 people from five Auto 2000 branch office in Jakarta . The results of the data showed that most subjects utilizing humor as a way of reducing stress . Humor is used mostly quite aggressive humor and enjoy aggressive humor television scene. Aggressive humor is like mocking and bullying on someone. There is also the use of humor as a way to maintain relationships with others, such as negotiate with customers, which is associated with affliative humor . Keywords : Humor , salesperson , Indigenous Psychology